Modelling difficulties in abstract thinking in psychosis: the importance of socio-developmental background. Issue 1 (2nd January 2017) - Berg, A. O.; Melle, I.; Zuber, V.; Simonsen, C.; Nerhus, M.; Ueland, T.; Andreassen, O. A.; Sundet, K.; Vaskinn, A.
ABSTRACT: Introduction: Abstract thinking is important in modern understanding of neurocognitive abilities, and a symptom of thought disorder in psychosis. In patients with psychosis, we assessed if socio-developmental background influences abstract thinking, and the association with executive functioning and clinical psychosis symptoms. Methods: Participants ( n  = 174) had a diagnosis of psychotic or bipolar disorder, were 17–65 years, intelligence quotient (IQ) >  70, fluent in a Scandinavian language, and their full primary education in Norway. Immigrants ( N  = 58) were matched (1:2) with participants without a history of migration ( N  = 116). All participants completed a neurocognitive and clinical assessment. Socio-developmental background was operationalised as human developmental index (HDI) of country of birth, at year of birth. Structural equation modelling was used to assess the model with best fit. Results: The model with best fit, χ 2  = 96.591, df = 33, p  < .001, confirmed a significant indirect effect of HDI scores on abstract thinking through executive functioning, but not through clinical psychosis symptoms. Conclusions: This study found that socio-developmental background influences abstract thinking in psychosis by indirect effect through executive functioning. We should take into account socio-developmental background in the interpretation of neurocognitive performance in patients with psychosis, and prioritise cognitive remediation in treatment of immigrant patients.